2006
DOI: 10.1590/s1806-83242006000400012
|View full text |Cite
|
Sign up to set email alerts
|

Retention of radicular posts varying the application technique of the adhesive system and luting agent

Abstract: This study evaluated in vitro the retention of intracanal cast posts cemented with dual-cure resin varying the application method of the primer/adhesive solution and luting agent in the prosthetic space prepared to receive the posts. Sixty endodontically treated maxillary canines had their crowns discarded, and their roots were embedded in acrylic resin. The prosthetic spaces were prepared with Largo burs mounted on a low-speed handpiece coupled to a parallelometer in order to maintain length and diameter of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
(41 reference statements)
0
8
0
4
Order By: Relevance
“…12 In the event that these procedures are not possible, it is suggested that a beveled finish line be chosen so that a metal belt can embrace the root. The adhesive technique with resin composite and pre-fabricated fiber posts is recommended because it forms a single block between the root and the filling core.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In the event that these procedures are not possible, it is suggested that a beveled finish line be chosen so that a metal belt can embrace the root. The adhesive technique with resin composite and pre-fabricated fiber posts is recommended because it forms a single block between the root and the filling core.…”
Section: Discussionmentioning
confidence: 99%
“…The cement was mixed and introduced into the post spaces with a lentulospiral drill using a low-speed handpiece. 12 Cement was also applied on the posts before they were gently seated by finger pressure and held in place for 60 s. The cement was light polymerized for 30 s on each surface (buccal, palatal, mesial and distal), for a total 2-min light polymerization cycle.…”
Section: Methodsmentioning
confidence: 99%
“…Also the viscosity of the resin cement and the way the cement was placed into the post space seemed to be important factors that could affect the complete setting of fibre posts 12 and consequently the strength of the post retentive force. Although the mechanical properties of dual-cure resin cement have been evaluated, little information is available on the role of the application methods of dualcure resin cements into the post space and their effect on the regional bond strength of fibre post.…”
Section: Introductionmentioning
confidence: 99%
“…Já a seringa tipo Centrix (Centrix Inc.) e ponta aplicadora do tipo Accudose (Centrix Inc.,Shelton, CT, USA) foram originalmente desenvolvidas para inserção de cimento de ionômero de vidro, mas também podem ser utilizadas para a inserção do cimento no interior do canal radicular (11). Outra alternativa comumente utilizada na prática odontológica, pela facilidade e rapidez do método, é a inserção do cimento diretamente sobre o pino, e este, levado ao interior do conduto radicular (12).…”
Section: Introductionunclassified